Program Edukasi Gizi Seimbang Bagi Ibu Hamil Sebagai Strategi Pencegahan Keguguran (Miskram) - Andi Ernawati Manuntungi; Andi Hartati; Yarnita Yarnita; Irma Aswani; Sahalia Sahalia (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2026)
Miscarriage is one of the reproductive health problems that still frequently occurs in Indonesia, especially among pregnant women with poor nutritional status. This community service activity aims to increase the knowledge and awareness of pregnant women about the importance of balanced nutrition as a means of preventing miscarriage. The program was carried out by lecturers and students through an educational approach in Village X, in July–August 2025. The implementation methods included nutrition counseling, demonstrations on preparing balanced meals, and individual mentoring. The results of the activity showed a significant increase in participants' understanding of nutritional needs during pregnancy, as indicated by a 45% increase in knowledge scores compared to before the intervention. In addition, participants showed positive changes in their consumption of nutritious foods. This activity is expected to serve as an implementable model in supporting maternal and child health programs at the village level.